Language of Love in Marcelijus Martinaitis „Atmintys“ - Bačiulienė, Kristina (Respectus Philologicus, 2014)
The notion of transcendental love in the context of “the eternal return”, the motif of Eros, and the image of a woman are discussed in Marcelijus Martinaitis’s book “Atmintys: meilės lyrikos albumas” (Eng. Reminiscences: the album of love lyrics”) (2008). The methods of mythopoetic thought, comparativistics, and interpretative mind have been applied. On the basis of the Bible, mythology, the notion of and relation between Eros and Love, also combining notions developed by philosophers as Nikolai Berdyaev, Erich Fromm, Vladimir Solovyev, phenomenologists as Algis Mickūnas, Mircea Eliade, Plato, and insights by popes Paul VI and Benedict XVI, a concept which might be useful in deciphering the language of love in Marcelijus Martinaitis’s book is introduced. The primary code of the album of love is the concept of memory and the notion of love as seen by Oskaras Milašius, while the secondary code relates to Dante, chivalric romance of Provence troubadours, legends of King Arthur, Celtic mythology. The genre of M. Martinaitis’s reminiscences was born when the poet was studying in Gervinės, and the first collection of Reminiscences appeared in 1986. The text of Reminiscences was seen as hermetic, intertextual, reflecting the act of cosmogony and antropogony in permanent space-time. The process of word re-creation is associated with archetypal consciousness, and the cycle of “the eternal return” prevails. Love is perceived as transcendental and existential basis, a purpose to merge with God, God’s gift to humanity, and the vision of love object. Eros (passion) is ambivalent: it is earthly / heavenly, sinful / divine, creating / destructive, and driving power of creation. A woman is seen as earthly / sensual, divine / unreachable. An issue which motif (Christian or courtesan literature) dominates in the album of love lyrics is discussed. Album is of great interest as an immanent text.
Keywords: love; Eros; “the eternal return”; memory; courtesan love